RISAP Is a TGN-associated RAC5 effector regulating membrane traffic during polar cell growth in tobacco - Stephan, Octavian; Cottier, Stéphanie; Fahlén, Sara; Montes-Rodriguez, Adriana; Sun, Jia; Eklund, D. Magnus; Klahre, Ulrich; Kost, Benedikt (The plant cell, 2014)
RAC/ROP GTPases coordinate actin dynamics and membrane traffic during polar plant cell expansion. In tobacco (Nicotiana tabacum), pollen tube tip growth is controlled by the RAC/ROP GTPase RAC5, which specifically accumulates at the apical plasma membrane. Here, we describe the functional characterization of RISAP, a RAC5 effector identified by yeast (Saccharomyces cerevisiae) two-hybrid screening. RISAP belongs to a family of putative myosin receptors containing a domain of unknown function 593 (DUF593) and binds via its DUF593 to the globular tail domain of a tobacco pollen tube myosin XI. It also interacts with F-actin and is associated with a subapical trans-Golgi network (TGN) compartment, whose cytoplasmic position at the pollen tube tip is maintained by the actin cytoskeleton. In this TGN compartment, apical secretion and endocytic membrane recycling pathways required for tip growth appear to converge. RISAP overexpression interferes with apical membrane traffic and blocks tip growth. RAC5 constitutively binds to the N terminus of RISAP and interacts in an activation-dependent manner with the C-terminal half of this protein. In pollen tubes, interaction between RAC5 and RISAP is detectable at the subapical TGN compartment. We present a model of RISAP regulation and function that integrates all these findings.
Gesehen am 13.10.2020